2019
DOI: 10.1038/s41598-018-38316-6
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic and agronomic characterization of intergeneric hybrids between Saccharum spp. hybrid and Erianthus arundinaceus

Abstract: In sugarcane (Saccharum spp. hybrid) breeding, introgression of useful genes via intergeneric hybridization is a powerful strategy for improving the crop productivity. Erianthus arundinaceus shows great potential in terms of useful traits; however, little is known about the cytogenetic and agronomic characteristics of intergeneric hybrids between these two species. Here, we examine the cytogenetic and agronomic characteristics, and relationships between the two in intergeneric F1 hybrids between modern sugarca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 45 publications
1
25
0
Order By: Relevance
“…In the grass family (Poaceae) hybridisation and introgression are well studied mainly for economically important plants, such as wheats 17 , 18 , maize 19 , 20 , rice 21 , 22 , barley 23 , 24 , oats 25 , 26 , rye 27 , 28 , sugarcanes 29 , 30 , and sorghums 31 , 32 . Nowadays new molecular markers and technologies that first came to the field of agriculture are becoming widely used in studies of wild populations with little or no previous genomic information.…”
Section: Introductionmentioning
confidence: 99%
“…In the grass family (Poaceae) hybridisation and introgression are well studied mainly for economically important plants, such as wheats 17 , 18 , maize 19 , 20 , rice 21 , 22 , barley 23 , 24 , oats 25 , 26 , rye 27 , 28 , sugarcanes 29 , 30 , and sorghums 31 , 32 . Nowadays new molecular markers and technologies that first came to the field of agriculture are becoming widely used in studies of wild populations with little or no previous genomic information.…”
Section: Introductionmentioning
confidence: 99%
“…Due to F 1 male sterility, F 1 could only be used as the female parent, the offspring material could be obtained through backcrossing, and the chromosome transmission was 2n + n or more than 2n + n, which also made the BC 1 material richer in a variety of resistances and vitalities. E. arundinaceus chromosomes were also lost (28~29) in five hybrids [30]. When these hybrids were crossed with commercial varieties as female parents, the pattern of "2n + n" or more than "2n + n" was seen in BC 1 hybrids, and 23~36 E. arundinaceus chromosomes were present in these plants.…”
Section: Discussionmentioning
confidence: 98%
“…When these hybrids were crossed with commercial varieties as female parents, the pattern of "2n + n" or more than "2n + n" was seen in BC 1 hybrids, and 23~36 E. arundinaceus chromosomes were present in these plants. The fertility of BC 1 material was restored, and the restoration of the fertility of the offspring helped obtain "noble" hybrids with the advantages of high sugar content, high disease resistance, and strong tillers [30]. In general, low fertility and unbalanced hybridization in offspring were most likely related to abnormal meiosis processes.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, sugarcane breeders had been implemented wide hybridization between sugarcane and E. arundinaceus, despite the large genetic distance between sugarcane and E. arundinaceus. More delightfully, subsequent introgression generations had also been obtained in sugarcane breeding programs (Fukuhara et al 2013;Gao et al 2015;Govindaraj et al 2012;Pachakkil et al 2019;Wu et al 2014). Selecting introgression progeny with the best performance as good candidates are of vital importance for introgression breeding.…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, cytological methods and molecular markers are widely used to speci cally detect the alien chromosomes and chromosomal segments in putative progeny. Genomic in situ hybridization (GISH) is a powerful cytological tool for identifying the introgression status of alien chromosomes in sugarcane background (Pachakkil et al 2019;Piperidis et al 2010). GISH results of progeny between sugarcane and E. arundinaceus indicated that chromosome transmission was n + n in F 1 , BC 2 , and BC 3 generations, but was 2n+ n in BC 1 generation (Piperidis et al 2010;Wu et al 2014).…”
Section: Introductionmentioning
confidence: 99%